Blunted Nocturnal Salivary Melatonin Secretion Profiles in Military-Related Posttraumatic Stress Disorder - Paul, Michel A.; Love, Ryan J.; Jetly, Rakesh; Richardson, J. Donald; Lanius, Ruth A.; Miller, James C.; MacDonald, Michael; Rhind, Shawn G. (Frontiers in Psychiatry, 2019)
Background: Although sleep disturbances are a hallmark of posttraumatic stress disorder (PTSD), few studies have evaluated the role of dysregulated endogenous melatonin secretion in this condition. Methods: This study compared the sleep quality and nocturnal salivary melatonin profiles of Canadian Armed Forces (CAF) personnel diagnosed with PTSD, using the Clinician Administered PTSD Scale (CAPS score ≥50), with two healthy CAF control groups; comprising, a ‘light control’ (LC) group with standardized evening light exposure and ‘normal control’ (NC) group without restriction. Participants were monitored for 1-week using wrist actigraphy to assess sleep quality, and 24-h salivary melatonin levels were measured by immunoassay (sampling every 2 h) on the penultimate day in a dim-light (<5 lux) laboratory environment. Results: A repeated measures design showed that nocturnal (mean ± SEM) melatonin concentrations for LC were higher than both HC (p=.03) and PTSD (p=.001) with no difference between PTSD and HC. Relative to PTSD, HC had significantly higher melatonin levels over a 4-h period (01 h to 05 h), whereas the LC group had higher melatonin levels over an 8-h period (23h to 07 h). Actigraphic sleep quality parameters were not significantly different between healthy controls and PTSD patients, likely because the PTSD patients were taking sleeping medications. Conclusions: Blunted nocturnal melatonin secretion in military PTSD in association with sleep disturbances was consistent with previous findings showing lower melatonin after exposure to trauma and suggestive of severe chronodisruption. Future studies targeting the melatonergic system for therapeutic intervention may be beneficial for treatment resistant PTSD.